Twórczości poetki żeni wasylkiwskiej W dyskursie literackim “grupy nowojorskiej” - Karabowicz, Tadeusz; Karabovich, Tadeush (Східноєвропейський національний університет імені Лесі Українки, 2015)
Карабович Тадей. Творчість поетеси Жені Васильківської у літера- турному дискурсі Нью-Йоркської групи. У статті подано літературознавчий аналіз творчості поетеси Жені Васильківської в контексті її участі у дискурсі Нью-Йоркської групи. Автор доводить, що збереження цінностей української поезії на еміграції було актуальним завданням поетеси, яка народилася у місті Ковелі на Волині.Karabovich Tadeush. Creation of Poetess Zheni the Vasil’kivskoy in Literary Discourse New York Group. The paper presents a literary analysis of works by the Ukrainian female poet Zhenia Vasylkivska in the context of her participation in the discourse of the New York Group of Ukrainian émigré poets. The author proves that the preservation of values of Ukrainian poetry in exile was a pressing task forVasylkivska, who came from the town of Kovel in the Volhynia region.
Creation of Poetess Zheni the Vasil’kivskoy in Literary Discourse New York Group
Keywords: поезія; переклади; культура; естетика; еміграція; poetry; translations; culture; aesthetics; emigration